Persepsi Masyarakat Terhadap Iklan Rokok di Negeri Passo, Kecamatan Baguala, Kota Ambon - Yani Talakua (Universitas Trunojoyo Madura, 2018)
Smoking is a bad habit that has been done since the time of the discovery of tobacco. Initially smoking only aims to warm the body but, over time the habit becomes changed goal is as a requirement that can not be abandoned or can be said to be addicted. Without tobacco as if there is no pleasure in itself. This continued until the time of the industrial revolution in England until the emergence of cigarette factories to spread throughout the world. The majority of smokers worldwide are ± 47% male population while 12% are female population with different age categories. Various reasons people smoke a variety, among these people there are several factors that influence a person to smoke for example, prestige factors to be called